Effect of precooling and acclimation on repeat-sprint performance in heat - Brade, Carly; Dawson, B.; Wallman, K. (2013)
This study determined whether precooling would have an additive effect on repeat-sprint cycling performance in heat following partial acclimation. Ten males completed three trials; Pre Acclimation (Pre Acc) and two Post Acclimation trials, one with precooling (ice jacket and slushy; Post Acc +PC) and another without (Post Acc). Trials consisted of a 30-min baseline period followed by a 70-min repeat-sprint protocol in ~35°C and 60% relative humidity. Separating pre and post trials were five heat acclimation sessions. Although no significant differences were found for performance variables, inferential statistical analysis resulted in moderate effect sizes, which suggested more work (J · kg-1) was performed in Post Acc compared with Pre Acc. Further, 'possible' and 'very likely' benefits were found for every performance variable for Post Acc compared with Pre Acc, while 'possible' benefits were found for Post Acc, compared with Post Acc +PC, for peak power output (W and W · kg-1). Moderate to strong effect sizes suggested lower core temperatures in both post acclimation trials compared with Pre Acc. Sweat loss was significantly higher (P < 0.05; 23.1%) in Post Acc +PC compared to other trials. In conclusion, no additional performance enhancement was seen when partially acclimated individuals precooled prior to repeat-sprint performance in heat. © 2013 Copyright Taylor and Francis Group, LLC.